Dialogic Engagement and Institutional Trust: A Netnographic Study of @halal.indonesia on Instagram as a Government Communication Platform - Fadhli, Ahmad; Fahzaria, Nabilla Anasty; Indrawati, Izni Nur; Dewi, Iska Nur Indira; Ridzki, Megumi Zahira (Universitas Ahmad Dahlan, 2025)
This study explores how the Halal Product Guarantee Agency (BPJPH) utilizes selective engagement strategies on its official Instagram account, @halal.indonesia, to map public interest and prioritize communication. As Indonesia holds the world's largest Muslim population and serves as a global halal market leader, strategic public communication around halal certification is critical. Employing a qualitative netnographic method, this research analyzes 1,502 Instagram posts and 27,943 associated comments published between May 2019 and February 2024. The analysis reveals that while all posts received engagement, dialogic interaction occurred in only 2.68% of comments, and administrative responses were identified in just 319 comment threads—42.78% of dialogic interactions and only 0.21 per upload on average. Administrator responses were concentrated around posts offering public service information, halal certification processes, and policy outreach. These findings suggest that BPJPH practices intentional and selective responsiveness, favoring comments that reflect high public interest or information-seeking behavior, while disregarding vague, low-quality, or off-topic content. The study underscores the significance of strategic two-way communication in cultivating institutional trust, transparency, and participatory governance in digital spaces. It contributes to the discussion on social media governance, interest mapping, and digital public engagement, offering practical implications for communication strategies across public sector institutions.